Current understanding and distinct features of multifocal and multicentric breast cancers - Elizabeth Avera; Lilia Valentic; Loan Bui (Cancer Reports, 2023)
Abstract Background Multifocal (MF) and multicentric (MC) breast cancers are referred to as synchronous, multiple ipsilateral breast cancers; however, the definitions vary among the literature, which has made understanding and analyzing these diseases challenging. Recent findings The incidence ranges from 1% to 60%, with a higher prevalence in pre‐menopausal women. MF and MC breast cancers, compared with unifocal breast cancers, tend to be more aggressive and are associated with lower survival rates, higher recurrence, and lymph node metastasis. Typically, patients with MF/MC breast cancers are treated with radical surgery, while breast conservation therapy may also be considered. Investigations have focused on elucidating the distinct biological features of MF/MC breast cancers, including the clonality of the cancers, the genetic alterations, and the impact of these features on disease aggressiveness and patient prognosis. Conclusion These findings will broaden the understanding of these breast cancer subtypes and aid in the development of more tailored treatment plans for patients.